2020
DOI: 10.1007/s10560-020-00698-w
|View full text |Cite
|
Sign up to set email alerts
|

Youth Leaving Institutional Care in China: Stress, Coping Mechanisms, Problematic Behaviors, and Social Support

Abstract: The study aims to provide an initial depiction of youth aging out of institutional care in China. Services for children cared in state child welfare institutes have been improving in the past decades in China. Lately, there is increasing consensus about the need for further understanding and alleviating challenges faced by youth who are aging out of the institutional care and transitioning to adulthood. Programs aimed at providing transitional services and support for these youth have emerged. However, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(49 reference statements)
0
13
0
1
Order By: Relevance
“…Delinquency was the second most commonly reported form of high-risk behavior in the included studies (Table 5). In three studies, delinquency was divided based on manifestation and severity (Cusick et al, 2012;Liu et al, 2020;van Breda, 2020). Adolescents who had been placed in out-ofhome care are at a 2.5 times greater risk of incarcerated relative to adolescents who have not been in out-of-home care (Yang et al, 2017); furthermore, each additional placement increases the risk for arrest by 4% (Cusick et al, 2012).…”
Section: Delinquencymentioning
confidence: 99%
See 2 more Smart Citations
“…Delinquency was the second most commonly reported form of high-risk behavior in the included studies (Table 5). In three studies, delinquency was divided based on manifestation and severity (Cusick et al, 2012;Liu et al, 2020;van Breda, 2020). Adolescents who had been placed in out-ofhome care are at a 2.5 times greater risk of incarcerated relative to adolescents who have not been in out-of-home care (Yang et al, 2017); furthermore, each additional placement increases the risk for arrest by 4% (Cusick et al, 2012).…”
Section: Delinquencymentioning
confidence: 99%
“…Adolescents who had been placed in out-ofhome care are at a 2.5 times greater risk of incarcerated relative to adolescents who have not been in out-of-home care (Yang et al, 2017); furthermore, each additional placement increases the risk for arrest by 4% (Cusick et al, 2012). The prevalence of delinquent behavior ranged from approximately 2% (Liu et al, 2020) to almost 45% (Cusick et al, 2012). Most of the included studies reported that almost one-quarter of care leavers had committed crimes or were incarcerated (Cusick et al, 2012;Kelly, 2020;Mitchell et…”
Section: Delinquencymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of research, the field would benefit from additional longitudinal studies devoted to the health and wellbeing of adolescents and young adults with child welfare experience. To date there is a wealth of longitudinal datasets that explore risk and protective factors for mental health and life satisfaction in this population around the world [44][45][46][47][48]. However, for the large part they have not reported analysis of the relationships between/among sources and types of social supports and mental health status.…”
Section: Future Directionsmentioning
confidence: 99%
“…Este es uno de los principales desafíos para los procesos de protección: lograr dar cuenta de la garantía y protección de los derechos de las/os adolescentes que tienen a su cargo, sin caer en un excesivo grado de paternalismo que les impida a las/os jóvenes entrenarse en situaciones que deberán resolver por su cuenta una vez egresen. De igual forma, será muy importante reforzar estos aspectos teniendo en cuenta la complejidad de las políticas de empleo y de vivienda de ambos países, dando un lugar especial a las competencias de empleabilidad, las cuales han sido señaladas, de manera reiterada, como fundamentales en el tránsito a la vida adulta (Alonso Bello, Santana Vega & Feliciano García, 2018;Arnau-Sabatés, Marzo, Jairot & Sala-Roca, 2014;Liu et al, 2020;Souto-Otero, 2016).…”
Section: Discusión Y Conclusionesunclassified